Application of Chlorella sp. and Scenedesmus sp. in the Bioconversion of Urban Leachates into Industrially Relevant Metabolites - Jeimy J. Ortiz-Betancur; Marla S. Herrera-Ochoa; Janet B. García-Martínez; Néstor A. Urbina-Suarez; Germán L. López-Barrera; Andrés F. Barajas-Solano; Samantha J. Bryan; Antonio Zuorro (Applied Sciences, 2022)
This paper explores the ability of Chlorella sp. and Scenedesmus sp. to convert landfill leachates into usable metabolites. Different concentrations (0.5, 1, 5, and 10% v/v) of leachate coupled with an inorganic carbon source (Na2CO3, and NaHCO3) were tested to improve biomass production, metabolites synthesis, and removal of NO3 and PO4. The result shows that both strains can effectively grow in media with up to 5% (v/v) leachate, while significantly reducing the concentrations of NO3, and PO4 (80 and 50%, respectively). The addition of NaHCO3 as a carbon source improved the final concentration of biomass, lipids, carbohydrates, and the removal of NO3 and PO4 in both strains.